Access for all : building inclusive financial systems - Helms, Brigit (Books Ser., 2006)
"Access for All: Building Inclusive Financial Systems outlines the "new" vision of microfinance, laying out in plain language what CGAP and others in the development field have learned over the past 10 years about building inclusive financial systems. Access for All is neither a technical handbook nor a chronicle of the history of microfinance. Instead, it pulls together disparate sources of information to describe where the microfinance field finds itself in 2006, as well as the opportunities and challenges ahead." "Access for All will enable readers to quickly grasp the practical implications of a fairly murky concept - inclusive financial systems - by making a cogent argument about what we know now, what we need to find out, and where further information can be found."